2020
DOI: 10.3390/plants9020154
|View full text |Cite
|
Sign up to set email alerts
|

YES-10, A Combination of Extracts from Clematis mandshurica RUPR. and Erigeron annuus (L.) PERS., Prevents Ischemic Brain Injury in A Gerbil Model of Transient Forebrain Ischemia

Abstract: Clematis mandshurica RUPR. (CMR) and Erigeron annuus (L.) PERS. (EALP) have pharmacological effects including anti-inflammatory activity and been used in traditional medicines in Asia. However, neuroprotective effects of CMR and/or EALP extracts against brain ischemic insults have never been addressed. Thus, the aim of this study was to examine neuroprotective effects of YES-10, a combination of extracts from CMR and EALP (combination ratio, 1:1), in the hippocampus following ischemia/reperfusion in gerbils. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…YES-10 ® was prepared as previously described in our published paper ( 5 , 30 ). Briefly, CMR and EALP were cultivated in Metro-Mix potting soil with a slow releasing fertilizer (Osmocote Plus).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…YES-10 ® was prepared as previously described in our published paper ( 5 , 30 ). Briefly, CMR and EALP were cultivated in Metro-Mix potting soil with a slow releasing fertilizer (Osmocote Plus).…”
Section: Methodsmentioning
confidence: 99%
“…The administration of the vehicle or YES-10 ® was orally given with a feeding needle once/day for 7 days because extracts from natural products have orally been ingested in traditional medicine. The dose of YES-10 ® (200 mg/kg) was chosen on the basis of our published paper, in which pretreatment with 200 mg/kg of YES-10 ® strongly protected the pyramidal neurons located in the hippocampal CA1 field after TI ( 5 ). We applied 7 days for YES-10 ® administration according to previous studies with plant extracts, and since data regarding to ADME properties of YES-10 ® had been rarely reported ( 18 , 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been reported that a severer aspect of neuronal loss/death in the hippocampus is shown following 15 min of TFI than that in 5 min TFI in gerbils [ 2 ]. Furthermore, a rat model of focal brain ischemia induced by MCAO for over 1 h develops infarct lesion (necrotic tissue) which is easily visualized by 2, 3, 5-triphenyltetrazolium chloride (TTC) assay, but infarction does not occur in the brain induced by TFI for 5–15 min in gerbils when the TTC assay is applied, in which selective neuronal death only occurs [ 1 , 15 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%